2014
DOI: 10.1021/jp505021a
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Features of Photostimulated Oxygen Isotope Exchange and NO Adsorption on “Self-Sensitized” TiO2–x/TiO2 in UV–Vis Region

Abstract: We have investigated the photoactivated O 2 adsorption/desorption, the isotope equilibration (POIEq), and the isotope exchange (POIEx) in the O 2 −(TiO 2−x /TiO 2 ) (Degussa P-25) system, as well as the adsorption and POIEx in the NO−(TiO 2−x /TiO 2 ) systems. The photoactivation spectra of the hole centers O s − generation, of POIEq, and of the NO photoadsorption were measured in the 300−500 nm range using a continuously adjustable wavelength light source. The spectral characteristics of the NO photoadsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The photooxidation of lattice bound oxygen via photogenerated holes resulting in the release of molecular oxygen has been proposed as a mechanism for O 2 formation by Salvador 56 and for the gas phase photocatalytic oxidation of organic compounds by Pichat 57,58 and Lisachenko. 59 The idea behind the mechanism of photoelectronic processes including the excitation energy transfer to the surface-atom bond resulting in the formation of an oxygen vacancy is also supported by other experimental techniques such as ion and electron bombardment, where the kinetic energy of the accelerated ions is transferred to the TiO 2 lattice. 60,61 Actually, Fukushima et al 62 observed the anatase to rutile transition during the TiO 2 lm formation by means of ion bombardment.…”
Section: Papermentioning
confidence: 93%
“…The photooxidation of lattice bound oxygen via photogenerated holes resulting in the release of molecular oxygen has been proposed as a mechanism for O 2 formation by Salvador 56 and for the gas phase photocatalytic oxidation of organic compounds by Pichat 57,58 and Lisachenko. 59 The idea behind the mechanism of photoelectronic processes including the excitation energy transfer to the surface-atom bond resulting in the formation of an oxygen vacancy is also supported by other experimental techniques such as ion and electron bombardment, where the kinetic energy of the accelerated ions is transferred to the TiO 2 lattice. 60,61 Actually, Fukushima et al 62 observed the anatase to rutile transition during the TiO 2 lm formation by means of ion bombardment.…”
Section: Papermentioning
confidence: 93%
“…The kinetic equations for the calculation of R x , R q , and R PA from the kinetics of the partial pressures O 2 32 , O 2 34 , and O 2 36 are similar to those published in ref . Compared to ref , the present kinetics is complicated on account of the photoadsorption (formulas are provided in the Supporting Information).…”
Section: Resultsmentioning
confidence: 81%
“…The kinetic equations for the calculation of R x , R q , and R PA from the kinetics of the partial pressures O 2 32 , O 2 34 , and O 2 36 are similar to those published in ref . Compared to ref , the present kinetics is complicated on account of the photoadsorption (formulas are provided in the Supporting Information). R q is proportional to O 2 pressure, and the pressure changes slightly due to PA. To eliminate this dependency, we plot K q ≡ R q / N , where N is the number of O 2 molecules in the gas phase in a reactor chamber.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations